Women’s Land Ownership in Bihar: An Analysis of Socio-Legal Barriers and Structural Challenges - Amrit Warshini; Veenita Kumari; Aman Verma (Journal of Agricultural Extension Management, 2026)
Women’s land ownership still remains limited in Bihar, despite legal reforms to enhance gender equality in property rights. This study investigates barriers to land ownership for women farmers in Bihar’s Tirhut division, focusing on three districts: West Champaran, Muzaffarpur, and Sheohar. Using a mixed-methods approach, structured interviews and focus group discussions, captured quantitative and qualitative data from 120 farmers selected through a multi-stage sampling process. Findings reveal that only 7.5% of the surveyed women possess land titles, primarily obtained through inheritance. Barriers to ownership include financial constraints (63.1%), restrictive socio-cultural norms (18.0%), and limited awareness of land rights (18.9%). Correlation analysis indicates that ‘access to legal services’ (r=0.497) and ‘participation in community meetings’ (r=0.239) are significantly associated with land ownership, suggesting that legal support and community engagement are critical enablers. However, demographic factors like age, education, and income show no significant impact on ownership, underscoring the complex socio-legal landscape influencing women’s land rights. These results suggest empowering women through legal aid, enhanced community involvement, and targeted f inancial support could mitigate barriers, fostering greater land ownership and economic stability for women farmers in Bihar.